A central role for the acid sphingomyelinase/ceramide system in neurogenesis and major depression - Gulbins, Erich; Walter, Silke; Becker, Katrin Anne; Halmer, Ramona; Liu, Yang; Reichel, Martin; Edwards, Michael J.; Müller, Christian P.; Fassbender, Klaus; Kornhuber, Johannes (Journal of Neurochemistry, 2015)
Major depressive disorder is a severe and chronic illness with high lifetime prevalence and a high incidence of suicide as the cause of death for patients with this diagnosis. Major depressive disorder is often treated with anti-depressants. Although these drugs have been used for many years, their exact mode of action is still unknown. It has been suggested that many anti-depressants act by increasing the concentrations of serotonergic transmitters in the synaptic space. However, recent studies have examined the effects of anti-depressants on neurogenesis in the hippocampus, the restoration of hippocampal neuronal networks that may be affected by major depression, and the regulation of the hypothalamic-pituitary-adrenal axis by immature neurons in the hippocampus. Here, we present and discuss a novel hypothesis suggesting that these events are regulated by the concentrations of sphingolipids, in particular ceramide, in the hippocampus. These concepts suggest that the acid sphingomyelinase/ceramide system plays a central role in the pathogenesis of major depression and may be a novel target for anti-depressants.
EVALuna2:23711